Penilaian Postur Tubuh Pekerja Dan Perbaikan Sistem Kerja Dengan Metode Rula Dan Reba Pada Pt. Sharp Electronics Indonesia - Esa Julian Firdaus; Kusnadi Kusnadi; Prabowo Angga Sujarno (Jurnal Serambi Engineering, 2023)
In the current industrial age, Indonesia is making great progress every year. Especially in the development of business competition for goods and services, businessmen compete with each other to dominate the market share on which they are focused.One of the inseparable factors of industry is human resources. It is very important to maintain the quality of human resources in order to continue the production process. So ergonomics is important to keep people healthier, safer, more comfortable and avoid bad parts (bad). PT Sharp Electronics Indonesia is one of the electronic companies of Sharp Corporation engaged in the assembly of electronic products. One of the manufactured products is a refrigerator. There are some quality issues in the production process. This means that defects are often still found on the assembly line. This adds to the cost of poor quality because if a defect occurs, the part must be reworked or the part scrapped. One of the causes is improper posture, which can have a big impact on the operator's body later on. A proposed solution to this problem is to use the RULA and REBA methods to find the worker's posture rating and correct it if the posture is bad.